2003
DOI: 10.5194/acp-3-925-2003
|View full text |Cite
|
Sign up to set email alerts
|

Ground-based PTR-MS measurements of reactive organic compounds during the MINOS campaign in Crete, July–August 2001

Abstract: Abstract. This study presents measurements of acetonitrile, benzene, toluene, methanol and acetone made using the proton-transfer-reaction mass spectrometry (PTR-MS) technique at the Finokalia ground station in Crete during the Mediterranean INtensive Oxidant Study (MINOS) in JulyAugust 2001. Three periods during the campaign with broadly consistent back trajectories are examined in detail. In the first, air was advected from Eastern Europe without significant biomass burning influence (mean acetonitrile mixin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
99
2
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(114 citation statements)
references
References 43 publications
10
99
2
3
Order By: Relevance
“…Observations of enhanced SO 2 over Southeastern Europe by GOME (Eisinger and Burrows, 1998) as well as the fact that during NE directions about 70% of the SO 2 column can be attributed to lignite combustion in power plants in Bulgaria and Romania (Zerefos et al, 2000), can help to explain the maxima in aerosol loadings from the easterly sector. Biomass burning from areas at the northern coast of the Black Sea (Salisbury et al, 2003;Balis et al, 2003b) may also contribute episodically. Cleaner conditions, associated with fine aerosol particles, are found for the NW direction, in spite of the presence of the most industrialized countries of Central Europe being in this sector.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations of enhanced SO 2 over Southeastern Europe by GOME (Eisinger and Burrows, 1998) as well as the fact that during NE directions about 70% of the SO 2 column can be attributed to lignite combustion in power plants in Bulgaria and Romania (Zerefos et al, 2000), can help to explain the maxima in aerosol loadings from the easterly sector. Biomass burning from areas at the northern coast of the Black Sea (Salisbury et al, 2003;Balis et al, 2003b) may also contribute episodically. Cleaner conditions, associated with fine aerosol particles, are found for the NW direction, in spite of the presence of the most industrialized countries of Central Europe being in this sector.…”
Section: Discussionmentioning
confidence: 99%
“…This can be attributed to the fact that sources of pollution with different seasonal characteristics (central heating, transportation, industrial activities etc.) are superimposed on the seasonality related to the change of (Salisbury et al, 2003;Balis et al, 2003b).…”
Section: Seasonality Of Aerosol Optical Propertiesmentioning
confidence: 99%
“…Good alternatives, however, are not readily available. Some authors have suggested the use of methanol as a biogenic tracer [Salisbury et al, 2003], but this work will show that primary anthropogenic sources of this VOC are also significant.…”
Section: Data Descriptionmentioning
confidence: 99%
“…The MINOS (Mediterranean INtensive Oxidant Study) campaign (Lelieveld et al, 2002;Salisbury et al, 2003) took place in summer 2001 (28 July till 21 August) with the objective to study the chemical and transport processes that cause the relatively high pollution concentrations often encountered in the Eastern Mediterranean lower atmosphere (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%